Pengaruh Aksesibilitas Terhadap Pendapatan Masyarakat Desa (Studi Kasus : Desa Batu Belah dan Desa Ranah Baru, di Kecamatan Kampar, Riau) - Astrid Laura Pasaribu (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2022)
This study aims to determine the effect of road length, number of businesses, educational facilities, and APBD on Village Community Income (Case Study: Batu Belah Village and Ranah Baru Village, Kampar District, Riau). The method used in this research is descriptive and quantitative methods of correlation type. The population in this study is Batu Belah Village and Ranah Baru Village, Kampar District, Riau Province. Data collection techniques using documentation. Analysis of the data used is Multiple Linear Regression with processing using SPSS Version. 25.00. The results of this study indicate that partially and simultaneously the variable length of the road, number of businesses, educational facilities, and APBD affect the income of the people in Batu Belah Village and Ranah Baru Village.